Utilization of Mobile-Based Educational Applications (E-Stunted) to Improve Mothers’ Knowledge About Stunting: A Quasi-Experimental Study - Sigit Ambar Widyawati; Alfan Afandi; Kustiyono; Irwan Budiyono; Solikah; Dina Lusiana Setyowati (Journal of Health Education, 2026)
Background: Stunting remains a major public health concern in Indonesia, particularly in rural areas where access to health education is limited. Enhancing maternal knowledge through digital interventions offers a promising solution.. Objective: This study aimed to evaluate the effectiveness of a mobile-based educational application (E-Stunted) in improving maternal knowledge about stunting prevention. Methods: A quasi-experimental design with a non-equivalent control group pretest- posttest was conducted in Brebes, Indonesia. A total of 138 mothers of children under five were purposively assigned to either an intervention group (n=70) that received the E-Stunted application or a control group (n=68) that received standard health education. Knowledge scores were measured using a validated 20-item questionnaire before and after the 7-day intervention. Statistical analysis included paired and independent t-tests, and Cohen’s d to assess effect size. Results: The intervention group showed a significant increase in knowledge scores from 10.7 ± 2.8 to 16.2 ± 2.1 (p<0.001), while the control group improved modestly from 10.5 ± 2.7 to 12.1 ± 2.5 (p<0.001). Between-group differences post-intervention were statistically significant (p<0.001), with a large effect size (Cohen’s d = 1.58).  Conclusions: The E-Stunted application significantly improved maternal knowledge on stunting prevention and holds potential as a scalable digital health education tool in rural settings.